2020
DOI: 10.1021/acsami.0c05286
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanocomposites Complexed with Gold Nanoparticles on Polyaniline and Application to Their Nerve Regeneration

Abstract: Electrically conductive materials can stimulate stem cells through electric shock and thereby contribute to the regulation of cell proliferation and differentiation. Recently, polymer–metal complexes composed of polyaniline and gold nanoparticles have emerged as novel candidates for use in regenerative medicine. By mixing two different materials, such composites maximize the benefits while alleviating the disadvantages of using either material alone. Based on their excellent conductivity, these complexes can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The most common method is the addition of carbon nanotubes into the matrix (Jahromi et al, 2020; Sun et al, 2020; Zhang et al, 2015). Similar studies have been performed with gold nanoparticles, which also have excellent electrical conductivity supporting neuronal development (Kim et al, 2020). However, similar to carbon structures, their systemic toxicity due to the nondegradability of these nanostructures is still controversial (Chen, Hung, Liau and Huang, 2009).…”
Section: Introductionsupporting
confidence: 57%
“…The most common method is the addition of carbon nanotubes into the matrix (Jahromi et al, 2020; Sun et al, 2020; Zhang et al, 2015). Similar studies have been performed with gold nanoparticles, which also have excellent electrical conductivity supporting neuronal development (Kim et al, 2020). However, similar to carbon structures, their systemic toxicity due to the nondegradability of these nanostructures is still controversial (Chen, Hung, Liau and Huang, 2009).…”
Section: Introductionsupporting
confidence: 57%
“…Native axons are subject to cyclic electric impulses in order to transfer information. Therefore, appropriate electrical stimulation for cells encapsulated in the scaffolds and host neurons and glia is speculated to promote axon survival and migration [ 220 , 221 ]. Dong et al incorporated graphene into electrospun fibrous scaffolds, and they found that electrical stimulation could accelerate cell migration and promote neurotrophic factor secretion in vitro as well as enhance sciatic nerve regeneration and functional recovery after implantation [ 222 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Metallic nanoparticles such as AuNPs have been also able to endow electrical conductivity to the polymer matrices for regulation of neural cell differentiation. Hybrid nanocomposites based on AuNP complexes with polyaniline enabled electrical stimulation . Particularly, microtubule-associated BMP-2 was prominently expressed, and the stimulation process led the neurites to grow from the stem cells.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Hybrid nanocomposites based on AuNP complexes with polyaniline enabled electrical stimulation. 359 Particularly, microtubule-associated BMP-2 was prominently expressed, and the stimulation process led the neurites to grow from the stem cells. Peripheral nerve regeneration can be also enabled by layered electrospun scaffolds based on Fe 3 O 4 magnetic nanoparticles and melatonin.…”
Section: Biomedical Applicationsmentioning
confidence: 99%